Tuna, Tempe, and Moora-Based Nuggets Prevent Stunting: Organoleptic Tests, Water Content, and ASH Content - Joyeti Darni; Retno Wahyuningsih (Jurnal Gizi Prima (Prime Nutrition Journal), 2023)
Background: Stunting is associated with suboptimal brain development, which has long-term implications for cognitive abilities, school performance, and future employment. There is a relationship between fish consumption and the incidence of stunting in children. Fish nuggets are one alternative to increase fish consumption. Fish nuggets combination of tempeh and moringa leaves can be taught to the community to increase children's protein intake. The nugget formulation used consists of 60% tuna, 20% tempeh, and 20% moringa leaves. The purpose of this study was to determine organoleptic tests, water content and ash content of nuggets made from a mixture of tuna, tempeh and moringa leaves.Research Methods: This study is an experimental research. The research was conducted in the laboratory of the Faculty of Food Technology and Agroindustry, University of Mataram to analyze the water content and ash content of nuggets. Research was also conducted at the taste test laboratory of the Health Polytechnic of the Ministry of Mataram.Research Result: Overall reception 60% Panelists really liked the nuggets made from Tuna, Tempeh and Moringa Leaves. Water content and ash content meet the quality requirements of SNI fish nuggets.Conclusion: The results of the organoleptic test with the parameters of color, taste, aroma, texture, and overall acceptability concluded that the overall acceptability was 60%. Panelists liked Tuna, Tempeh, and Moringa fish-based nuggets. The water and ash content meet the SNI quality requirements for fish nuggets.